TINGKAT KECEMASAN ANAK DALAM PENCABUTAN GIGI DI PUSKESMAS MUTIARA - Reca Reca; Citra F Putri; Teuku Salfiyadi; Cut Aja Nuraskin; Ainun Mardiah (Jurnal Online Keperawatan Indonesia, 2020)
Children’s anxiety in dental care may lead to uncooperative attitudes. It will reduce the efficiency and effectiveness of dental health service. Based on preliminary survey which conducted at Public Health Center Mutiara, Pidie, Aceh, Indonesia, found that from around 10 children who had tooth extraction, 7 of them was overanxious which 2 children was failed to treat. But, there is still no clear data about the level of children’s anxiety in Public Health Center Mutiara. The purpose this study was to determine the level of children’s anxiety in tooth extraction in Public Health Center Mutiara, Pidie, Aceh, Indonesia. This descriptive research carried out from 10 June to 10 July 2019, by observing using a checklist sheet. The sample was carried out by accidental sampling method. Thirty children with aged 6-12 years old who had tooth extraction was selected in this study. The results showed that majority children (40%) was in severe anxiety, 10% children was no anxiety, 20% children was mild anxiety, and 30% was moderate anxiety. It show that the tooth extraction teratment may not be success because the high level of children’s anxiety, so that the parents and health workers can motivate children to take care of their teeth and can anticipate anxiety that occurs in children.